Evaluation of KV Reduction on image quality in OPG X-Ray (Indian Journal of Forensic Medicine & Toxicology, 2020)
Panoramic radiographs are widely used to obtain an overall survey of the maxillofacial complex. One of the advantages is the reduction in radiation dosage compared with complete intraoral radiography. Digital imaging was first introduced in dentistry for intra-oral radiography. but is now widely available for panora micradiography. Many studies have demonstrated that it is possible to achieve a degree of dose reduction in digital panoramic radiography.
Keywords: K? , Reductio?; imag? qualit?; O?? ?-Ra?